The Role of Teachers in Applying A Humanistic Approach to Foster Self-Confidence in Upper-Grade Elementary School Students - Lestari, Puji; Agustina, Sari; Yullahna, Weny Waly; Ayunah, Ayunah; Rahmaini, Beti (Jurnal Likhitaprajna, 2026)
This qualitative case study aims to explore how upper-grade elementary school teachers foster students’ self-confidence through humanistic classroom practices. The study was conducted at SDN 1 Ulak Balam in South Sumatra, Indonesia. Data were collected through classroom observations, semi-structured interviews, and document analysis involving three teachers, six students with varying levels of self-confidence, and one school principal selected purposively. Data were analyzed using an interactive model. The findings reveal that teachers consistently applied supportive and empathetic approaches in their daily instruction, despite limited formal training in pedagogy. Various instructional strategies—such as structured questioning, small-group activities, and inclusive participation—were found to encourage student engagement and confidence. A strong emotional connection between teachers and students emerged as a key facilitating factor, while differences in student personalities and fear of peer judgment posed notable challenges. These results underscore the importance of providing structured professional development in student-centered teaching approaches and promoting school-wide efforts to create safe and supportive learning environments that enhance student self-confidence.